2015
DOI: 10.3389/fpls.2015.00079
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis flower specific defense gene expression patterns affect resistance to pathogens

Abstract: We investigated whether the Arabidopsis flower evolved protective measures to increase reproductive success. Firstly, analyses of available transcriptome data show that the most highly expressed transcripts in the closed sepal (stage 12) are enriched in genes with roles in responses to chemical stimuli and cellular metabolic processes. At stage 15, there is enrichment in transcripts with a role in responses to biotic stimuli. Comparative analyses between the sepal and petal in the open flower mark an over-repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 72 publications
3
18
0
Order By: Relevance
“…The increased expression of defense response genes in ant ail6 may be a consequence of sepals making up a larger part of ant ail6 flowers as compared with wild-type flowers. A recent analysis of publicly available transcriptomic data showed that defense genes are some of the most abundant transcripts in stage 12 to 15 sepals, suggesting that sepals play a key role in pathogen defense of the flower (Ederli et al, 2015). Thus, the increased defense gene expression in ant ail6 may partly or fully be an indirect effect resulting from changes in floral organ identity present in the double mutant.…”
Section: Functional Categorization Of Differentially Expressed Genesmentioning
confidence: 99%
“…The increased expression of defense response genes in ant ail6 may be a consequence of sepals making up a larger part of ant ail6 flowers as compared with wild-type flowers. A recent analysis of publicly available transcriptomic data showed that defense genes are some of the most abundant transcripts in stage 12 to 15 sepals, suggesting that sepals play a key role in pathogen defense of the flower (Ederli et al, 2015). Thus, the increased defense gene expression in ant ail6 may partly or fully be an indirect effect resulting from changes in floral organ identity present in the double mutant.…”
Section: Functional Categorization Of Differentially Expressed Genesmentioning
confidence: 99%
“…Our inclusive analysis revealed 405 that the majority of transcripts that are significantly differentially expressed in infected snails are 406 downregulated relative to uninfected snails. This pattern could reflect several non-mutually 407 exclusive phenomena, ranging from tissue/organ destruction and/or overall poor condition of 408 infected snails (e.g., Barribeau et al 2014) to reallocation of resources to genes needed for 409 defence against and response to Microphallus infection (e.g., Ederli et al 2015) to suppression 410 and/or parasitic manipulation of P. antipodarum gene expression by Microphallus as a means of 411 evading host immune and defence systems (e.g., Levri & Lively 1996;Barribeau et al 2014;412 Soper et al 2014;de Bekker et al 2015). Regardless of the specific mechanism(s) involved, the 413 transcripts that are differentially expressed between infected and uninfected snails in the inclusive 414 analysis represent a set of genes that are most likely to be of general importance to the P. 415 antipodarum-Microphallus interaction.…”
mentioning
confidence: 99%
“…This pattern is observed both overall (inclusive analysis) as well as within two of the three lakes (Alexandrina and Kaniere). Such patterns have been observed in other hostparasite interactions whereby exposure to and/or infection by parasites lead to systematic downregulation (e.g., de Bekker et al 2015;Ederli et al 2015). I also found that gene expression responses to M. livelyi infection tend to be population specific.…”
Section: Genomic Evidence For Population-specific Responses To Coevolsupporting
confidence: 69%
“…antipodarum are characterized by systematic downregulation of genes relative to uninfected P. antipodarum. This result could reflect several non-mutually exclusive scenarios such as the destruction of tissue (e.g., , reallocation of resources for defense purposes (e.g., Ederli et al 2015), and/or suppression or manipulation of host defenses by M. livelyi (e.g., de Bekker et al 2015). I also found that patterns of differential gene expression between infected and uninfected snails tend to be population specific, which provides the first genomic evidence consistent with ecological evidence for local adaptation and coevolution in this system.…”
Section: Influence Of Ploidy Level and Reproductive Mode On Patterns mentioning
confidence: 95%
See 1 more Smart Citation